Going global? The engagements of Danish private foundations in international development cooperation - Adam Moe Fejerskov; Christel Rasmussen (Danish Institute for International Studies (DIIS), 2014)
During the past decade attention paid to the role of private foundations in international development cooperation has intensified, as several of these have increased their global giving and transformed their approach to philanthropy from reactive grant-making to strategic social impact. While having been identified in the macro context of the world's biggest foundations, we have yet to see if such processes have also occurred at micro-level. This working paper makes one such contribution by exploring the international activities of Danish foundations. It finds that while the bulk of these continue to have a domestic focus, grant-making on global issues is increasing. In parallel, several of the foundations have undergone transformations in organisation of and approach to grant-making, including the adoption of more specialised and strategic approaches. Many are building capacity to be involved not just in funding, but also project conception, implementation and evaluation, increasing their role in global issues.
Keywords: 330